EFEKTIVITAS DISCOVERY LEARNING BERBANTUAN MEDIA QUESTION CARD TERHADAP HASIL BELAJAR IPS SISWA KELAS IV SDN TENGGILIS MEJOYO - Muhammad Fahmi Amrullah; Triman Juniarso; Via Yustitia (LPPM Universitas Cipta Mandiri, 2022)
The purpose of the research was conducted by researchers to analyze the effectiveness of the Discovery Learning learning model assisted by the Question Card media on the learning outcomes of students in social studies learning class IV SDN Tenggilis Mejoyo I Surabaya1.This study uses a descriptive quantitative approach design, there are three analytical techniques used in this study, namely analysis of learning implementation observation, analysis of learning outcomes tests and analysis of learning interest questionnaires. In this study, the effectiveness of the application of the Discovery Learning model assisted by the Question Card media is described on the learning outcomes of students in social studies learning for class IV SDN Tenggilis Mejoyo I Surabaya.The results of observing the activities of researchers in knowing the effectiveness of the Discovery Learning model assisted by Question card media in learning Theme 4 Sub-theme 1 Types of work Learning 2 Class IV A SDN Tenggilis Mejoyo I Surabaya by researchers is said to be in the high category. 2. Student learning outcomes using the Discovery Learning model assisted by Question Card media in learning Theme 4 Sub-theme 1 Types of work Learning 2 Class IV A SDN Tenggilis Mejoyo I Surabaya in the form of a knowledge test to get an average score with a very good category. 3. Student responses to the Question card-assisted Discovery Learning model in learning Theme 4 Sub-theme 1 Types of work Learning 2 Class IV A SDN Tenggilis Mejoyo I Surabaya The academic year 2021/2022 received a positive response. Learning using the Discovery Learning model assisted by Question Card media in social studies learning on Theme 4 Subtheme 1 Types of work Learning 2 Class IV A SDN Tenggilis Mejoyo I Surabaya The academic year 2021/2022 can be said to be effective.